Plant extract from Caesalpinia spinosa inhibits cancer-associated fibroblast-like cells generation and function in a tumor microenvironment model - Jiménez, Maria Camila; Prieto, Karol; Lasso, Paola; Gutiérrez, Melisa; Rodriguez-Pardo, Viviana; Fiorentino, Susana; Barreto, Alfonso (Heliyon, 2023)
Interactions in the tumor microenvironment (TME) between tumor cells and stromal cells such as cancer-associated fibroblasts (CAF) favor increased survival, progression, and transformation of cancer cells by activating mechanisms of invasion and metastasis. The design of new therapies to modulate or eliminate the CAF phenotype or functionality has been the subject of recent research including natural product-based therapies. We have previously described the generation of a standardized extract rich in polyphenols obtained from the Caesalpinia spinosa plant (P2Et), which present antitumor activities in breast cancer and melanoma models through activities that modulate the metabolism of tumor cells or induce the development of the immune response. In this work, a model of CAF generation was initially developed from the exposure of 3T3 fibroblasts to the cytokine TGFβ1. CAF-like cells generated in this way exhibited changes in the expression of Caveolin-1 and α-SMA, and alterations in glucose metabolism and redox status, typical of CAFs isolated from tumor tissues. Then, P2Et was shown to counteract in vitro-induced CAF-like cell generation, preventing caveolin-1 loss and attenuating changes in glucose uptake and redox profile. This protective effect of P2Et translates into a decrease in the functional ability of CAFs to support colony formation and migration of 4T1 murine breast cancer tumor cells. In addition to the functional interference, the P2Et extract also decreased the expression of genes associated with the epithelial-mesenchymal transition (EMT) and functional activities related to the modulation of the cancer stem cells (CSC) population. This work is an in vitro approach to evaluate natural extracts’ effect on the interaction between CAF and tumor cells in the tumor microenvironment; thus, these results open the chance to design a more profound and mechanistic analysis to explore the molecular mechanisms of P2Et multimolecular activity and extent this analysis to an in vivo perspective. In summary, we present here a standardized polymolecular natural extract that has the potential to act in the TME by interfering with CAF generation and functionality.